ถอดบทเรียนการสร้างนักข่าวท้องถิ่นผ่านการผลิตหนังสือพิมพ์ฝึกปฏิบัติ - เอี่ยมเรไร ทิฆัมพร (Area Based Development Research Journal, 2015)
บทคัดย่อไม่สมบูรณ์ An evaluation of becoming a local journalist through a demonstrated newspaper abstract unavailable